The incidence, severity and mechanisms of injury across three levels of association football. - Hughes, M.; Craggs, B. (World Congress of Performance Analysis of Sport VIII, 2008)
The study revealed that as the standard of football increased so did the number of free-kicks, or foul incidents, awarded. A significant relationship was also discovered suggesting that across all three levels of football significantly more injuries were a result of non-foul situations (p < 0.05). Although no significant association was reported by the chi-squared test for the number of injuries occurring across the levels of football (p > 0.05), a relationship was discovered. The frequency of injuries increased in a negative correlation to the standard of football. The majority of injuries were caused from player-toplayer contact. Being tackled was found to cause the most injuries within the World Cup and Premiership, yet challenging for a header possessed the highest risk of injury within the Non-League. The chi-squared test revealed no significant association across the levels of football and injury mechanism (p > 0.05). No significant relationship between the frequency of injuries and the period of the match in which they occurred across all three levels of football, could be identified (p > 0.05). Within the World Cup defenders were at the greatest risk of injury however, the Premiership and Non-League found midfielders to be more frequently injured. This demonstrated no significant association between the levels of football and injuries occurring in different playing positions (p > 0.05). The lower extremities were prone to a greater amount of injuries than the upper extremities and head although no significant relationship was discovered for injury location and the levels of football (p > 0.05).